The relationship between tooth loss and cerebral stroke - Mitsuyoshi Yoshida; Yasumasa Akagawa (Elsevier, 2011)
Objective: Tooth loss has been suggested as a potential risk factor for cerebral stroke. This report reviews prospective studies investigating the association between tooth loss and stroke. Method: The PubMed database was used to identify studies about the relationship between tooth loss and stroke including prospective, cohort, and follow-up studies reported from 2000 to 2010. Results: Four prospective follow-up studies have been conducted on the relationship between tooth loss and stroke and three of four reports have suggested that tooth loss is related to incidence of both ischemic and hemorrhagic stroke. Conclusion: The results of this review study support the hypothesis that there is an association between early tooth loss and the occurrence of stroke.